High performance through business process management : strategy execution in a digital world - Kirchmer, Mathias, 1963- (Springer, 2017)
High Performance Through Process Excellence explores how business process management delivers real value in private and public sector organizations around the world. It is written for executives and managers as well as educators and students.
Keywords: Business -- Data processing.; Business -- Databases.; Management information systems.; elektronické knihy; electronic books